2016
DOI: 10.1111/bjd.14495
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopy, a useful tool for general practitioners in melanoma screening: a nationwide survey

Abstract: Summary Background Dermoscopy improves diagnostic accuracy in melanoma, as shown by several meta‐analyses. Although it is used by general practitioners (GPs) in Australia, Canada and Italy, no published data on this topic are available in France. Objectives To review the opinions and use of dermoscopy by GPs in France and to understand their practice of skin examination. Methods We designed a descriptive and cross‐sectional survey and conducted it between 26 November and 26 December 2014. An anonymous, multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
57
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 30 publications
5
57
0
1
Order By: Relevance
“…This is likely to be at least partly due to two‐thirds of our respondents reporting a personal history of dermatology posts and qualifications, in keeping with Australian evidence that GP subspecialisation in dermatology leads to increased rates of dermoscopy use . This very high level of dermoscopy use is closer to that of UK dermatologists in 2012 (99%), than for primary care practitioners internationally (34% in Australia in 2007 and 8% in France in 2016), or in our pilot survey of UK GPs without a special interest in dermatology ( n = 77, 17%) (unpublished data). Recent reviews of dermoscopy use for melanoma diagnosis point to an increase in diagnostic accuracy for benign lesions and melanoma when dermoscopy is used by trained GPs, and it can lead to a reduction in unnecessary referrals and excisions.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…This is likely to be at least partly due to two‐thirds of our respondents reporting a personal history of dermatology posts and qualifications, in keeping with Australian evidence that GP subspecialisation in dermatology leads to increased rates of dermoscopy use . This very high level of dermoscopy use is closer to that of UK dermatologists in 2012 (99%), than for primary care practitioners internationally (34% in Australia in 2007 and 8% in France in 2016), or in our pilot survey of UK GPs without a special interest in dermatology ( n = 77, 17%) (unpublished data). Recent reviews of dermoscopy use for melanoma diagnosis point to an increase in diagnostic accuracy for benign lesions and melanoma when dermoscopy is used by trained GPs, and it can lead to a reduction in unnecessary referrals and excisions.…”
Section: Discussionsupporting
confidence: 71%
“…However, there is no randomized controlled trial evidence comparing the effects of shorter and longer training periods. Previous studies have found that perceived training requirements are amongst the most commonly cited barriers to implementation of dermoscopy . This study suggests that 1 day of face‐to‐face training is sufficient to enable GPs with a special interest in dermatology to feel confident in dermoscopy use.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…There was a 63.5% reduction in the number of benign lesions requiring excision or referral from use of the dermoscopic intervention and sensitivity of diagnosis almost doubled. A recent study of French PCPs provides additional evidence supporting use of the dermascope for melanoma screening [20]. These studies suggest dermoscopy can improve the PCP’s diagnostic accuracy for skin cancer.…”
Section: Introductionmentioning
confidence: 96%